2022
DOI: 10.14569/ijacsa.2022.0130968
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis on Acceptance of New Normal in COVID-19 Pandemic using Naïve Bayes Algorithm

Abstract: The COVID-19 pandemic has such a significant impact and causes difficulties in many aspects that the new normal rules should be implemented to reduce the effects. New normal rules have been implemented by governments worldwide to break the virus chain and stop its transmission among the society. Even if the COVID-19 outbreak is under control, governments still need to know whether society could adapt and adjust to their new daily lifestyles. Many precautions still must be addressed as the transition to endemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(24 reference statements)
0
5
0
1
Order By: Relevance
“…Persamaan (4) menunjukkan bahwa c merupakan kelas atau label, dan x adalah vektor fitur yang dipakai untuk memprediksi kelas c. P(c|x) menunjukkan posterior probability suatu kelas yang diberikan fitur [20]. P(x|c) adalah likelihood, yaitu probability fitur x jika diketahui kelasnya c. P(c) adalah prior probability kelas, mewakili keyakinan awal tentang distribusi kelas.…”
Section: Klasifikasi Naive Bayes Classifierunclassified
“…Persamaan (4) menunjukkan bahwa c merupakan kelas atau label, dan x adalah vektor fitur yang dipakai untuk memprediksi kelas c. P(c|x) menunjukkan posterior probability suatu kelas yang diberikan fitur [20]. P(x|c) adalah likelihood, yaitu probability fitur x jika diketahui kelasnya c. P(c) adalah prior probability kelas, mewakili keyakinan awal tentang distribusi kelas.…”
Section: Klasifikasi Naive Bayes Classifierunclassified
“…The first research authors use one methodology for measurement sentiment analysis, shown in Table I. Authors in [10] have investigated the Naïve Bayes algorithm's capacity to classify public mood under COVID-19's new normal. From the 2807 tweets that have been processed, the test results show that Naïve Bayes has done an excellent job, with an accuracy of 83% and an F1score of 84%.…”
Section: A Previous Researchmentioning
confidence: 99%
“…Based on previous research, researchers will use the Naïve Bayes [10][13] [14], SVM [11][12] [13][15] [16], and CART [15] in evaluating sentiment analysis. In addition, the N-gram and TF-IDF methods will be used because they are proven to increase accuracy [16].…”
Section: A Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this industry is starting to bloom again with the lifting of all the Covid-19 restrictions and also the less severe effects of virus infections. In the early days of the opening of tourism, people have been educated about the new normal procedures such as wearing masks, social distancing and sanitizing hands [2]. Since then, people have not been afraid to go anywhere in the world for a holiday getaway.…”
Section: Introductionmentioning
confidence: 99%